2018
DOI: 10.1590/0037-8682-0044-2018
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of metallo-β-lactamase-encoding genes among carbapenem-resistant Pseudomonas aeruginosa strains isolated from burn patients in Iran

Abstract: Carbapenem-resistant Pseudomonas aeruginosa (CRPA) has been considered a major cause of infection and mortality in burn patients, especially in developing countries such as Iran. One of the most common mechanisms of carbapenem resistance is production of metallo-β-lactamases [(MBLs), including Verona Integron-encoded Metallo-beta-lactamase (VIM), imipenemase (IMP), São Paulo metalo-beta-lactamase (SPM), German imipenemase (GIM), New Delhi metallo-beta-lactamase (NDM), Dutch imipenemase (DIM), AIM, Seoul imipen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 26 publications
1
10
2
1
Order By: Relevance
“…Similarly, a study from Japan which included 180 P. aeruginosa reported that bla IMP-1 was the predominant gene detected (116/180 isolates) followed by bla VIM-2 (63/180 isolates) [16]. While a meta-analysis from Iran which included P. aeruginosa from burn patients reported that the pooled prevalence of bla VIM was 21.4% and of bla IMP was 13.1%, the reported rates were higher than in this study [30]. A study from Iran also reported that bla VIM (17.5%) was the most common gene followed by bla IMP (15.6%) [15].…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Similarly, a study from Japan which included 180 P. aeruginosa reported that bla IMP-1 was the predominant gene detected (116/180 isolates) followed by bla VIM-2 (63/180 isolates) [16]. While a meta-analysis from Iran which included P. aeruginosa from burn patients reported that the pooled prevalence of bla VIM was 21.4% and of bla IMP was 13.1%, the reported rates were higher than in this study [30]. A study from Iran also reported that bla VIM (17.5%) was the most common gene followed by bla IMP (15.6%) [15].…”
Section: Discussioncontrasting
confidence: 74%
“…A much higher rate was reported from Russia (75.3%) and Costa Rica (63.1%) [9]. A meta-analysis from Iran, which included 14 publications on P. aeruginosa isolated from burn patients, reported a pooled prevalence rate of 76.8% carbapenemresistant P. aeruginosa, which is much higher than that reported in this study [30]. However, a study from China, which included P. aeruginosa isolated from cystic fibrosis patients, reported that 56.25% of their isolates were found to be MBL producers, which is comparable to that reported in this study [21].…”
Section: Discussioncontrasting
confidence: 71%
“…13 In the present study, there were five IMP-positive strains (15.5%) and four VIM-positive strains (12.5%), similar to the results reported previously. 14,15 However, 27 strains were SIM-positive (84.4%), which was the most prevalent MBL gene in our study. This result is inconsistent with previous studies, maybe due to the difference in antibiotic usage in different areas.…”
Section: Discussionmentioning
confidence: 48%
“…In recent years carbapenem resistance in A. baumannii isolates are increasing in the world. Various factors have been mentioned to contribute to this outbreak, for example, inadequate implementation of treatment instructions and protocols, excessive use of antimicrobial agents in health care systems or the community [139,140] . It is suggested that controlling policy including standard administration guidelines together with the suitable drug, dosage as well as the duration of treatment should meticulously be monitored in order to prevent the emergence of resistance among bacteria.…”
Section: Discussionmentioning
confidence: 99%